2021
DOI: 10.1136/thoraxjnl-2020-216271
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of smooth muscle Rac1 in severe asthma-associated airway remodelling

Abstract: BackgroundSevere asthma is a chronic lung disease characterised by inflammation, airway hyperresponsiveness (AHR) and airway remodelling. The molecular mechanisms underlying uncontrolled airway smooth muscle cell (aSMC) proliferation involved in pulmonary remodelling are still largely unknown. Small G proteins of the Rho family (RhoA, Rac1 and Cdc42) are key regulators of smooth muscle functions and we recently demonstrated that Rac1 is activated in aSMC from allergic mice. The objective of this study was to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…For these reasons, it is not surprising that this Rho GTPase is now viewed as a potential target to treat various oncologic and non-oncologic diseases [ 30 ]. The list of pathologies addressable with Rac1 inhibitors has expanded significantly in recent years to include diabetes, neurodevelopmental disorders, pulmonary hypertension, asthma and other pathologies [ 25 , 128 , 129 , 130 , 131 ]. In cancer, Rac1 is receiving more and more attention given the large implications of the protein in metastasis, drug resistance and immune modulation [ 43 , 46 , 132 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For these reasons, it is not surprising that this Rho GTPase is now viewed as a potential target to treat various oncologic and non-oncologic diseases [ 30 ]. The list of pathologies addressable with Rac1 inhibitors has expanded significantly in recent years to include diabetes, neurodevelopmental disorders, pulmonary hypertension, asthma and other pathologies [ 25 , 128 , 129 , 130 , 131 ]. In cancer, Rac1 is receiving more and more attention given the large implications of the protein in metastasis, drug resistance and immune modulation [ 43 , 46 , 132 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rac1 contributes to the regulation of blood pressure and the pathogenesis of pulmonary hypertension [ 25 ]. The protein is implicated in asthma-associated airway remodeling [ 130 ] and other pathophysiological processes. The focus on bladder presented here shall not underestimate the potential benefit of targeting Rac1 in other pathologies.…”
Section: Rac1 Outside Bladdermentioning
confidence: 99%
“…The excessive proliferation of ASMC not only promotes the occurrence of airway hyperresponsiveness but also can modify the extracellular matrix and promote the production of inflammatory factors to further aggravate airway inflammation, which seriously affects the prognosis of asthma patients. 54 In vitro experiments have shown that icariin can not only induce S phase acceleration and G2/M phase arrest of airway smooth muscle cells to inhibit cell proliferation but also promote the expression of apoptosis-related genes to promote cell apoptosis. 55 In addition, a study using ovalbumin (OVA)-induced asthmatic mice conducted by Lingli Hu et al demonstrated that icariin intervention can significantly downregulate the expression of TGF-β1, vascular endothelial growth factor (VEGF), IL-13 (interleukin-13), endothelin-1 (ET-1), and other important cytokines in airway remodeling, inhibiting the activity of the MAPK/Erk signaling pathway and thereby inhibiting the proliferation of AMSCs and improving the airway remodeling process by affecting multiple targets.…”
Section: Icariin Could Inhibit Airway Smooth Muscle (Asmc) Proliferationmentioning
confidence: 99%
“…Studies have shown that Rac1 plays an important role in the contraction of various smooth muscles, such as bronchial smooth muscle, bladder smooth muscle, and prostate smooth muscle (180)(181)(182)(183). Although both EHT1864 and NSC23766 are Rac1 inhibitors, they have different pharmacological mechanisms in the inhibition of different smooth muscles (182,184,185), and EHT1864 tends to perform better (186,187). In recent years, new Rac1 inhibitors have been continuously developed.…”
Section: General Rac1 Inhibitormentioning
confidence: 99%